More of the same? The return to bicameral congress - Bullard González, Alfredo (2019)
After the rejection of bicameralism on December 9, 2018’s referendum, everything suggests that the opportunity for a major change was lost. The project subjected to the referendum was quite bad. However, its rejection is not so bad news. It provides the opportunity to a more consistent and technical reform. It is true that sometimes more from something bad sounds as something worse. More congressmen, for some, sounds frightening. However, there are strong reasons to believe that a bicameral congress, even with more congressmen, is better than a unicameral one with fewer congressmen. In this paper, the authors analyze how bicameralism allows that bills are passed by groups that represent most of the population, product of a broader political consensus. It allows that higher quality bills pass, as a consequence of a better process of scrutiny and reflection. Interestingly, raising transaction costs of the legislative process reduces the number of bills and improves the quality of the ones that pass. A bicameral congress creates incentives for the members of both lower and upper houses to fulfill their functions properly, especially when the electoral system is based on small constituencies (uninominal districts for deputies and binominal for senators).